Sexualidade de idosas institucionalizadas: percepção da equipe de enfermagem - Venturini, Larissa (2017)
Population aging has led to the development of studies about the different aspects that involve the elderly, including sexuality and Long-Term Care Institutions for the Elderly. Institutionalization may lead to a decrease in autonomy and loss of identity, thus interfering with the expression of the sexuality of the elderly. Sometimes manifestations of sexuality in old age can easily be perceived as a behavioral problem and not as an expression of a basic human need for love and intimacy. By tinkering the experience of the elderly in ILPI, it is considered that the nursing team plays a central role in care. In this context, understanding how the nursing team perceives the sexuality of institutionalized elderly women assumes relevance, since it can be expanded and contribute to care actions in this dimension. Faced with these settings, the objectives of the study are: to know the conceptions of sexuality for nursing workers in a LTIPI; To know the perception of the nursing team about the sexuality of institutionalized elderly women; And to know how the nursing team conducts the issues of sexuality in the daily life of the institutionalized elderly women. In order to answer the research objectives, a field research was carried out, with a descriptive character with a qualitative approach. The participants of the research were professionals of the nucleus of the nursing that work in an Institution. The data were obtained through a semistructured interview, combined with a technique of creativity and sensitivity called "Almanaque", developed from April to July 2016. Data analysis was based on the Pecheutiana Discourse Analysis. The ethical aspects of human research were respected following Resolution 466/12 of the National Health Council. The analysis of subjects' discourses was organized into three themes: conceptions about sexuality by nursing professionals; Sexuality of institutionalized elderly: perspectives of nursing professionals; And the nursing team 's work on issues related to the sexuality of institutionalized elderly women. The ideological, discursive and imaginary formations permeated the subjects' discourse, questioning the understanding of sexuality, its institutional conformation and the performance spent under the manifestations of the sexuality of the elderly. In this perspective, impasses and embarrassment can be observed in discussions about sexuality. Understanding the expressions of elderly women's sexuality from the perspective of nursing professionals has identified a number of barriers to their expression, such as the lack of privacy, professional attitudes, and the physical and psychological limitations established. In this way, understanding the key elements that influence the way of managing the sexuality of elderly women living in a nursing home made it possible to improve their understanding of their manifestations and behaviors in a female institution.